Labor Day [videorecording (DVD)] - Reitman, Jason, 1977-; Reitman, Jason, 1977-; Winslet, Kate; Brolin, Josh; Griffith, Gattlin; Maynard, Joyce, 1953- (Paramount, 2017)
A lonely, divorced mother allows an escaped killer to stay with her and her thirteen-year-old son.